Drugs and the Efforts to Overcome it in Jayawijaya Regency - Telly Nancy Silooy; Girinius Wenda (Jurnal Honai, 2021)
The widespread circulation of drugs in the community and the magnitude of the adverse effects and losses, both economic losses and social losses caused by it, have opened awareness from various circles to drive a "war" on drugs. In this study, several data collection techniques was used: Documents; used to examine existing data in the form of journal policy documents and books related to the research theme, as well as in-depth interviews and in analyzing the data SWOT analysis was used. The result of the study indicate that drugs control is not optimal. This is due to the lack of knowledge, skills, and attitudes possessed by the Narcotics Investigators in dealing with drugs crime cases. The inhibiting factors of efforts to improve the ability of investigators of the Narcotics Investigation Unit are external environmental factors as opportunities as well as threats, including: political, socio-cultural and technological factors. The inhibiting factors for drugs control efforts in Jayawijaya Regency are internal environmental factors as strengths as well as weaknesses, including: human resources, budget, facilities and infrastructure and communication factors. In order to suppress drugs criminal acts, the efforts that need to be carried out in overcoming drugs crimes in Jayawijaya Regency are: a.The existence of regional government policies to formulate drugs crimes prevention regulations; b.The policy of Jayawijaya Government in forming the Regency Narcotics Agency; c. Increasing the role of community leaders and religious leaders and NGOs involvement in suppressing drugs criminal acts; d. Maximizing socialization on every opportunity either formal and informal to overcome the drugs crimes; e. Increasing the availability of the budget in financing the addition of narcotics criminal acts adapted to regional conditions; f. Increasing the availability of human resources in quantity and quality; g. Improvement of adequate facilities and infrastructure; h. Coordination between agencies involved; and i. Increasing cooperation and communication in the prevention of drugs crimes.